Socially optimal contribution rate and cap in a proportional (DC) pension system - Simonovits, András (2015)
In our model, the government operates a mandatory proportional (DC) pension system to substitute for the low life-cycle savings of the lower-paid myopic workers, while maintaining the incentives of the higher-paid far-sighted ones in contributing to the system. The introduction of an appropriate cap on pension contribution (or its base)—excluding the earnings above the cap from the contribution base—raises the optimal contribution rate, helping more the lower-paid myopic workers and reserving enough room for the saving of higher-paid far-sighted ones. The social welfare is almost independent of the cap in a relatively wide interval but the maximal welfare is higher than the capless welfare by 0.3–4.5 %.